Predictive Value of Fasting Blood Glucose for Microvascular Obstruction in Nondiabetic Patients with ST-Segment Elevation Myocardial Infarction after Primary Percutaneous Coronary Intervention - Han Wu; Ran Li; Kun Wang; Dan Mu; Jian-Zhou Chen; Xuan Wei; Xue Bao; Zhong-Hai Wei; Jun Xie; Biao Xu (Cardiology Research and Practice)
Background. The relationship between fasting blood glucose (FBG) and microvascular obstruction (MVO) after primary percutaneous coronary intervention (PCI) remains unclear in nondiabetic patients with ST-segment elevation myocardial infarction (STEMI). This study aimed to determine the predictive value of FBG in MVO in nondiabetic STEMI patients. Methods. A total of 108 nondiabetic STEMI patients undergoing primary PCI were enrolled in this study. The patients were classified into either the MVO group or non-MVO group based on cardiac magnetic resonance imaging (CMR). Results. FBG in the MVO group was higher than in the non-MVO group. Univariate analysis showed that FBG, peak high-sensitive troponin T (TnT), pre-PCI thrombolysis in myocardial infarction (pre-PCI TIMI) flow, left ventricular ejection fraction (LVEF), infarction size, left ventricular end-diastolic diameter (LVEDd), left ventricular end-diastolic volume (LVEDV), and global longitudinal strain (GLS) were likely predictive factors of MVO. After adjustment for other parameters, FBG, peak TnT, LVEF, and LVEDV remained independent predictors for MVO. Conclusion. FBG was independently associated with MVO in nondiabetic STEMI patients.